EduVR: Towards an Evaluation Platform for User Interactions in Personalized Virtual Reality Learning Environments - Viol, Robson Santiago; Fernandes, Paula Cintra; Lacerda, Iago Izidório; Melo, Koda Gabriel Faria; Nunes, Arilton Junior De Aguilar; Pimenta, André Schneider Guimarães Montresor; Carneiro, Cláudia Martins; Silva, Mateus Coelho; Delabrida, Saul (Anais do Simpósio Brasileiro sobre Fatores Humanos em Sistemas Computacionais (IHC), 2023)
Integrating novel technologies in education, namely technology- enhanced learning (TEL), is broadly discussed in educational and technology development areas. It is understood that educators can improve their comprehension of each student’s learning processes using gathered data and provide more personalized content using technology. This work proposes a novel solution to automating getting data from interactions executed in Virtual Reality. This system offers a user-friendly interface allowing educators to create and share multimedia content in the game, collect data to provide insights about the users’ behavior based on his interactions with the system, and provide an analytic tool for feedback and future analysis. The system’s design discusses the main lessons learned by analyzing the theoretical concepts, functional and non-functional requirements, and the architecture proposal.